1996
DOI: 10.1111/j.1600-0536.1996.tb02220.x
|View full text |Cite
|
Sign up to set email alerts
|

Contact allergy to gold sodium thiosulfate

Abstract: 100 consecutive patients routinely attending the contact dermatitis clinic were patched tested to gold sodium thiosulfate (GST). 13 patients had a positive patch test to GST, 11 of whom were female, and 12 had pierced ears. There was no correlation with any other substance in the European standard series, although there was a high incidence of nickel sensitivity in all patients (33%). Eczema on the ring fingers and neck was significantly more common in the group positive to GST. 1/2 of the patients with a posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 13 publications
0
32
0
Order By: Relevance
“…[57][58][59][60][61] We found a rate of positive patch test reactions to gold sodium thiosulfate 2.0 pet of 22%, and to 0.5 pet of 20% in those tested. However, relevance could not be found in most (92 and 80%, respectively) of these cases.…”
Section: Notable Exclusions To the Australian Baseline Seriesmentioning
confidence: 72%
“…[57][58][59][60][61] We found a rate of positive patch test reactions to gold sodium thiosulfate 2.0 pet of 22%, and to 0.5 pet of 20% in those tested. However, relevance could not be found in most (92 and 80%, respectively) of these cases.…”
Section: Notable Exclusions To the Australian Baseline Seriesmentioning
confidence: 72%
“…Other studies have shown varying rates of positive reactions to gold ranging from 3.2% to 13%. [6][7][8][9][10][11][12] An interesting feature of gold allergy is the propensity for facial and eyelid dermatitis to occur. In 1988, Fowler 2 reported 2 women with eyelid dermatitis and gold allergy.…”
Section: Discussionmentioning
confidence: 99%
“…Many persons are or may be exposed to metallic gold as it is present in jewellery and dental materials (24)(25)(26)(27)(28)(29)(30)(31)(32)50). To act as a sensitizer, gold, like other metals, has to be ionized.…”
Section: Demonstration Of Present Exposurementioning
confidence: 99%
“…Can jewellery sensitize (27,(61)(62)(63)? The question of whether dental gold is significant for sensitization should be addressed further (25,26,28,29,32,50). Late-appearing positive patch test reactions to gold do not need to be examples of active sensitization (38) but, actually, the possibility of active sensitization as the explanation for a part of the lateappearing reactions has not been investigated and is thus not excluded.…”
Section: Need For Scientific Investigationsmentioning
confidence: 99%
See 1 more Smart Citation